DEVELOPMENT OF ORGANIZATIONAL AND ECONOMIC MECHANISMS TO ENHANCE ENTERPRISE EFFICIENCY IN THE DIGITAL ECONOMY - Mamarakhimov Bekzod Erkinovich (Modern American Journals, 2025)
This article examines the mechanisms for improving enterprise efficiency in the context of the digital economy. Digital technologies, such as artificial intelligence, big data, and automation, provide modern enterprises with opportunities to optimize workflows, reduce costs, and strengthen customer relationships. The article analyzes digital transformation processes, new business models, and innovative strategies.
Keywords: Digital, Transformation, Enterprise, Efficiency, Technological.